Investor sentiment and market reaction: evidence on 2010 FIFA World Cup - Vieira, Elisabete F. Simões
The purpose of this study is to examine whether investor sentiment influences the stock price reaction to football matches results, giving some contribute to the behaviour finance, or if investors react in a rational way, giving evidence of standard finance. To proxy for investor sentiment, we analyse the 2010 FIFA World Cup of South Africa. Globally, the study provides no evidence of a direct relationship between games results and the subsequent market reaction, not documenting a change in investor mood caused by soccer games outcomes. This paper contributes to the recent literature on the asset pricing impact of behaviour biases. The global results are more in line with standard finance than on behaviour finance, suggesting that stock prices are not influenced by economically-neutral events that can affect the investor sentiment, and, consequently, the stock prices.